2016
DOI: 10.1155/2016/2076921
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐Articular Hyaluronic Acid Compared to Traditional Conservative Treatment in Dogs with Osteoarthritis Associated with Hip Dysplasia

Abstract: The purpose of this study was to compare the efficacy of the intra-articular (IA) hyaluronic acid injection to traditional conservative treatment (TCT) in dogs with osteoarthritis (OA) induced by hip dysplasia. Sixteen dogs were distributed into two groups: Hyal: IA injection of hyaluronic acid (5–10 mg), and Control: IA injection with saline solution (0.5–1.0 mL) in combination with a TCT using an oral nutraceutical (750–1000 mg every 12 h for 90 days) and carprofen (2.2 mg/kg every 12 h for 15 days). All dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
16
1
1
Order By: Relevance
“…The efficacy of the intra-articular hyaluronic acid injection was also compared to traditional conservative treatment in 16 dogs with osteoarthritis. Clinical parameters improved in the HA-treated group from 15 to 90 and 60 to 90 days, compared to the control group (Carapeba et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The efficacy of the intra-articular hyaluronic acid injection was also compared to traditional conservative treatment in 16 dogs with osteoarthritis. Clinical parameters improved in the HA-treated group from 15 to 90 and 60 to 90 days, compared to the control group (Carapeba et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Among them, hyaluronic acid (HA), a large glycosaminoglycan present in the synovial fluid and with reduced concentration in patients with knee OA (Balazs et al, 1967;Altman, 2003), has been investigated. High molecular weight hyaluronic preparation hylan GF-20, a commercially available hydrogel, is a cross-linked preparation of hyaluronan with a molecular weight of 6,000 kDa (Pavelka and Uebelhart, 2011) which has been successfully used as viscosupplementation for knee OA in humans and dogs (Pavelka and Uebelhart, 2011;Shen et al, 2014;Carapeba et al, 2016). However, the effect of viscosupplementation is limited, so that it could be increased and particularly extended for longer periods by the combination with MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…High molecular weight HA reduces chemotaxis and migration of inflammatory cells, leading to a reduction in inflammation, and additionally protects against free radicals [14]. Several clinical trials have shown a slowdown in OA during HA treatment [15][16][17]. In addition, HA has an analgesic effect in OA [14,18].…”
Section: Review and Disscusionmentioning
confidence: 99%
“…Patients under 65 with a low OA severity are a group of patients who will definitely feel the beneficial effect of HA viscosupplementation [35]. HA can be recommended for both preventive and therapeutic use of IA as an anti-inflammatory agent, reducing the severity of symptoms and modifying the course of the disease [15][16][17].…”
Section: Review and Disscusionmentioning
confidence: 99%
“…Some of the medications or supplements used are nonsteroidal anti-inflammatory drugs, pain relief medication, antioxidants, and chondroprotective drugs (2,4,6). Another treatment modality still little explored in the treatment or prevention of naturally acquired osteoarthritis in dogs is viscosupplementation (8)(9)(10). Viscosupplementation refers the intra-articular administration of exogenous hyaluronic acid, or hyaluronic acid derivatives to provide pain relief and improve joint mobility (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%